2023
DOI: 10.1002/gps.5886
|View full text |Cite
|
Sign up to set email alerts
|

Using digital technologies to facilitate social inclusion during the COVID‐19 pandemic: Experiences of co‐resident and non‐co‐resident family carers of people with dementia from DETERMIND‐C19

Abstract: Background The COVID‐19 pandemic triggered rapid and unprecedented changes in the use of digital technologies to support people's social inclusion. We examined whether and how co‐resident and non‐co‐resident family carers of people with dementia engaged with digital technologies during this period. Methods Throughout November 2020‐February 2021, we interviewed 42 family carers of people with dementia from our DETERMIND‐C19 cohort. Preliminary analysis was conducted through Framework analysis, followed by an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…Like other studies on the use of digital technologies involving persons with dementia and their caregivers (47,51,50,53), our findings suggest that, while virtual participation was not a perfect replacement for in-person collaborative activities, virtual CCE offered meaningful connection and stimulation to all team members during the COVID-19 pandemic. This was especially true for peer collaborators with lived experience of dementia and their care partners who were are at greater risk of more extreme isolation.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Like other studies on the use of digital technologies involving persons with dementia and their caregivers (47,51,50,53), our findings suggest that, while virtual participation was not a perfect replacement for in-person collaborative activities, virtual CCE offered meaningful connection and stimulation to all team members during the COVID-19 pandemic. This was especially true for peer collaborators with lived experience of dementia and their care partners who were are at greater risk of more extreme isolation.…”
Section: Discussionsupporting
confidence: 70%
“…Since the "pandemic pivot", research has begun to emerge about online programs for older adults, including people living with dementia. Despite widespread prejudice around older adults that predicted their limited capacity with technology, older adults are reported to have used digital technology during COVID-19 to connect socially, access resources, and manage isolation (46,47). A systematic review by Rai et al of digital technologies specifically for people living with dementia, reported evidence that "technologies hold potential to improve quality of life and reduce isolation/loneliness for people with dementia" (48).…”
Section: Literature Review Of Related Workmentioning
confidence: 99%
“…One support avenue for dyads in the event of a future pandemic could involve training carers and people with dementia to use technology. This could help keep non-co-residents connected and allow co-residents carers to connect with other forms of social support ( Hicks et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of these challenges, carers are likely to support the digital engagement of people living with dementia 24 . However, this adds to the already heavy workload of many carers and assumes they have the digital skills and knowledge required to fully benefit from digitised services 25–27 . There is therefore pressing need for targeted interventions that enable people with dementia and carers from any background to access support, to prevent existing inequalities and the ‘digital divide’ being exacerbated by the increasing digitisation of dementia care 21,23,28 …”
Section: Introductionmentioning
confidence: 99%
“…24 However, this adds to the already heavy workload of many carers and assumes they have the digital skills and knowledge required to fully benefit from digitised services. [25][26][27] There is therefore pressing need for targeted interventions that enable people with dementia and carers from any background to access support, to prevent existing inequalities and the 'digital divide' being exacerbated by the increasing digitisation of dementia care. 21,23,28 Inequalities in dementia care tend to be explored in individual countries and often without an intersectionality approach, thereby focusing on a single specific potential barrier to care, such as age, ethnicity, or rural/urban living location.…”
mentioning
confidence: 99%